Species differentiation within the Staphylococcus intermedius group using a refined MALDI‐TOF MS database. (14th June 2014) - Murugaiyan, J.; Walther, B.; Stamm, I.; Abou‐Elnaga, Y.; Brueggemann‐Schwarze, S.; Vincze, S.; Wieler, L. H.; Lübke‐Becker, A.; Semmler, T.; Roesler, U.; Greub, G.
Abstract Among coagulase‐positive staphylococci of animal origin, the members of the Staphylococcus intermedius‐group (SIG: S. intermedius, Staphylococcus pseudintermedius and Staphylococcus delphini) are important opportunistic pathogens in different animal hosts and occasionally in humans. However, the unambiguous species diagnosis of SIG is often challenging. Therefore, matrix‐assisted laser desorption ionization—time of flight mass spectrometry (MALDI‐TOF MS) ‐based SIG‐identification with Bruker Microflex LT in combination with Biotyper 3.0 software (Bruker Daltonics, Bremen, Germany) was evaluated using (i) the original database content and (ii) the database after extension with distinct hierarchical clustered reference spectra for 60 SIG. A convenience sample comprising 200 isolates was used to compare both database performances. As a result, 17 isolates initially diagnosed as S. intermedius with the current content of the Bruker database were identified as S. pseudintermedius by applying the in‐house reference spectra extended version. Furthermore, a significant improvement (average rise of log score value: 0.24) of the SIG identification score values was achieved, emphasizing that further sequence‐based refinement of the Bruker database content allows improvement of MALDI‐TOF MS‐based identification.